Exercise-induced PGC-1α transcriptional factors in skeletal muscle - Suryun Jung; Kijin Kim (Integrative Medicine Research, 2014)
Skeletal muscle is adapting to the needs of the body by changes of various gene expression that control mitochondrial biogenesis, angiogenesis, and the composition of muscle fiber types. Recently, it was revealed that PGC-1α, which is an auxiliary transcription factor, plays a key role in the aforementioned adaptation phenomena. It means that various signal transduction systems within muscle directly affect the expression and activation of PGC-1α and also PGC-1s activates various programs for muscle adaptation. Therefore, this review assessed PGC-1α to understand the reaction and adaptation phenomena of muscle against the biological stimulus such as exercise and came to the conclusion that PGC-1α and PGC-1β significantly affect skeletal muscle in various ways, and also have an affect on the increase of exercise capacity, inducing of angiogenesis and the prevention of muscle atrophy and degeneration.